Evidências sobre diferencial de rendimentos entre o setor público e privado - uma análise do setor bancário - Ximenes, Tulia de Lima (2019)
This paper investigates the income differential between the financial sector worker linked to the public employer of that linked to the private employer. The differential of incomes paid by the public sector and by the private sector is a relevant study subject in the applied economics area and in general, literature shows that the public sector pays a higher wage to the worker compared to the private sector. The approach was based on the Mincerian equations in which we use the ordinary least squares method and the Oaxaca Blinder decomposition. The database used was extracted from the RAIS for the years 2013, 2015 and 2017. The results showed that there is a favorable wage gap for bank workers linked to financial institutions under public control, converging with the literature on the subject and even though this gap increased over the studied period from 37% to 41%. When we consider the decomposed factors, both the portion explained by the appropriations and the unexplained portion showed variations over time. In 2013 and 2015 the coefficient effect, unexplained portion, represented around 50% of the total private public wage gap. In 2017, this unexplained portion represented 62.7% of the total wage differential. As for the endowment effect, the share of the wage gap explained by the average characteristics of the workers linked to the public employer in 2013 and 2015 explained around 24% of the wage differential and in 2017 explained around 35% of the wage gap.